Expert System to Identify Typhus Using the Fuzzy Tsukamoto Method - Siti Fatimah Rambe (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
At RS. Hajj is clearly seen when the patient consults about typhus, the patient first mentions the complaints he is feeling, and after that the patient has to do another blood test to the laboratory and the results will come out 1 day after the patient's blood test is done, this is felt to be ineffective and requires long enough to find out whether the patient has typhus or not, the authors provide a solution to help ease the work of staff and doctors at the hospital. Hajj by creating an expert system to identify typhus using the Tsukamoto fuzzy method, before the authors make the system, of course the authors have to do research - what are the symptoms that often appear in patients with typhus at the hospital. Hajj, and the author gets 6 symptoms, namely body temperature, heart rate, headache, stomach ache, muscle aches, and tongue color. After that the writer made a system using the Tsukamoto fuzzy method. The Tsukamoto fuzzy method is first entered into a variable, the variable here is how many symptoms will be discussed, namely there are 6 symptoms, after that it is entered into the fuzzy set in the form of names and numbers, after that it is entered again into the knowledge base (rule-based). The expert only inputs patient data, patient consultation data is only enough to tell the expert what the complaints are and the expert will enter it into the system and enter the fuzzy set in the form of the name and number earlier, and the expert only needs to click the process button, the results of the patient having the disease will appear. low-risk typhoid, moderate, or high. And if the expert clicks the save button, the patient data for the consultation will automatically be stored in the identification and the expert can make a patient identification data report directly from the system that the author made without having to be afraid of errors, for example the date of the consultation, the patient's name because the author has made this system as much as possible. This system is built using the Java programming language and MySQL database.